DIE REHOBOTH-BASTERS: KONSTITUSIONELE NOODROEP VAN 'N MINDERHEIDSGROEP IN SUIDWES-AFRIKA (NAMIBIE), 1915-1939 (Historia, 2021)
The Rehoboth Basters : constitutional distress call from a minority group in South-West Africa (Namibia), 1915-1939 Baster-South African relations during the initial years of the Mandate following the First World War were marked by delicate constitutional negotiations. In spite of opposition, the Baster Council accepted a constitutional agreement in August 1923. Malcontents, however, initiated an effective protest by electing their own council. Efforts at mediation were largely unsuccessful. In December 1924 the South African government was faced with a unilateral declaration of independence, but in April 1925, it forced a showdown and subjected the rebels to its authority. Judge De Villiers, who had been appointed to investigate the Baster issue, delayed the submission of the report and this caused great frustration in Baster ranks. So much so, that the malcontents appeared to the League of Nations and the Governor General countless times. A Baster Advisory Council was instituted in April 1928. The new management body was boycotted by the Majority Party. In August 1932, however, the leader of the malcontents and a large number of his followers, motivated by the advice of the League of Nations and the economic woes of the early thirties, joined the Minority Party. A largely united Baster community then tried in vain to regain their self government. Baster-Suid-Afrikaanse betrekkinge tydens die aanvangsjare van Mandaatbestuur ná die Eerste Wêreldoorlog is gekenmerk deur delikate grondwetlike onderhandelinge. Ondanks teenkanting het die Basterraad in Augustus 1923 'n grondwetlike ooreenkoms aanvaar. Die ontevredenes het daarop met 'n effektiewe versetaksie begin deur 'n eie raad te verkies. Bemiddelingspogings is met bloedweinig sukses bekroon, en in Desember 1924 is die Suid-Afrikaanse Regering met 'n eensydige onafhanklikheidsverklaring gekonfronteer. Met groot magsvertoon het die Suid-Afrikaanse Regering die opstandelinge in April 1925 tot oorgawe gedwing. Die gesloer met die verslag van regter De Villiers, aangewys om die Basterkwessie te ondersoek, het groot frustasie in Bastergeledere veroorsaak. Male sonder tal het die ontevredenes hulle op die Volkebond en die Goewerneur-Generaal beroep. 'n Baster Adviserende Raad is in April 1928 ingestel. Die nuwe bestuursliggaam is deur die Meerderheidsparty geboikot. In Augustus 1932 het die kaptein van die ontevredenes en 'n hele aantal van sy volgelinge, gemotiveer deur die advies van die Volkebond en die ekonomiese ellende van die vroeë dertigerjare, hulle by die Minderheidsparty aangesluit. 'n Grotendeels verenigde Bastergemeenskap het daarna tevergeefs probeer om weer selfbestuur te bekom.
Keywords: Rehoboth; namibia; namibie; WWI; 1923; 1924; Baster advisory council; League of Nations; Minority Party; Baster adviserende raad; minderheidsparty; Historia; Suid-Afrikaanse geskiedenis; South African History